2021
DOI: 10.1002/1878-0261.12976
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling mutational dynamics in non‐small cell lung cancer patients by quantitative EGFR profiling in vesicular RNA

Abstract: The mutational status of the epidermal growth factor receptor (EGFR) guides the stratification of nonsmall cell lung cancer (NSCLC) patients for treatment with tyrosine kinase inhibitors (TKIs). A liquid biopsy test on cell-free DNA is recommended as a clinical decision supporting tool, although it has limited sensitivity. Here, we comparatively investigated the extracellular vesicle (EV)-RNA as an independent source for multidimensional and longitudinal EGFR profiling in a cohort of 27 NSCLC patients. We intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The molecular cargo of an individual EV and the heterogeneity within an EV population is lost in bulk‐level analyses. Recently, several new analytical methods, such as total internal reflection fluorescence microscopy (TIRFM), [ 6 ] digital PCR, [ 7 ] microarray‐based chip, [ 8 ] and high‐sensitivity flow cytometry combined with qPCR, [ 9 ] have been used to quantify a specific miRNA or mRNA in an single‐EV or small identical subpopulations. However, a high‐throughput analysis for the RNA profile of a single‐EV is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular cargo of an individual EV and the heterogeneity within an EV population is lost in bulk‐level analyses. Recently, several new analytical methods, such as total internal reflection fluorescence microscopy (TIRFM), [ 6 ] digital PCR, [ 7 ] microarray‐based chip, [ 8 ] and high‐sensitivity flow cytometry combined with qPCR, [ 9 ] have been used to quantify a specific miRNA or mRNA in an single‐EV or small identical subpopulations. However, a high‐throughput analysis for the RNA profile of a single‐EV is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…One group has shown that EVs can be sequestered in the droplets prior to lysing, enabling the detection of nucleic acid biomarkers from a single EV [ 75 ]. Using the ddPCR system from BioRad to digitize EVs into droplets, Pasini et al detected EGFR mutations (specifically L858R and T790M) in vesicular RNA.…”
Section: Advances In Methods For Single Ev Analysismentioning
confidence: 99%
“…Notably, a robust method was developed for detecting mutations in EV-RNA using droplet digital PCR (ddPCR) and was validated with Sanger sequencing with mutations found with over 90% sensitivity. The study profiled EVs before treatment and at the time of progression events in a cohort of metastatic NSCLC patients, further demonstrating the promise of using EV-RNA to monitor mutations through treatment ( Pasini et al, 2021 ). There remains, however, a need to verify whether changes in mutation burden, at either the RNA or protein level, found within EVs, is a predictor of progression events as opposed to a result of disease progression.…”
Section: Introductionmentioning
confidence: 93%
“…Several recent works have demonstrated the feasibility of using EV-RNA to detect EGFR mutations from blood ( Dong et al, 2019 ; Pasini et al, 2021 ) and bronchoalveolar lavage fluid ( Hur et al, 2019 ; Liam et al, 2020 ). Notably, a robust method was developed for detecting mutations in EV-RNA using droplet digital PCR (ddPCR) and was validated with Sanger sequencing with mutations found with over 90% sensitivity.…”
Section: Introductionmentioning
confidence: 99%